2020
DOI: 10.1186/s12872-020-01499-w
|View full text |Cite
|
Sign up to set email alerts
|

Relation between quantity and quality of peri-coronary epicardial adipose tissue and its underlying hemodynamically significant coronary stenosis

Abstract: Background: We aimed to investigate the association of lesion-specific epicardial adipose tissue (EAT) volume and density with the presence of myocardial ischemia. Methods: We enrolled 45 patients (55 lesions) with known or suspected coronary artery disease who underwent coronary computed tomography angiography (CTA) followed by invasive fractional flow reserve (FFR) assessment within 30 days. EAT volume (index) and density in patient-, vessel-and lesion-level were measured on CTA images. Lesion-specific ische… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Some investigations have shown that EAT volume was associated with myocardial ischemia detected by nuclear imaging (28,29), but the relationship between EAT volume and abnormal FFR remained unclear. Romijn et al (15) indicated that EAT volume could independently predict FFR dropping while other works arrived at contrary results (13,14,16). The reason for this debate could be explained by the patient population included in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some investigations have shown that EAT volume was associated with myocardial ischemia detected by nuclear imaging (28,29), but the relationship between EAT volume and abnormal FFR remained unclear. Romijn et al (15) indicated that EAT volume could independently predict FFR dropping while other works arrived at contrary results (13,14,16). The reason for this debate could be explained by the patient population included in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Standard quantitative coronary analysis (QCA) was used to quantify the ICA stenosis severity with the method as previously described. FFR was performed with a coronary pressure wire (Volcano, Rancho Cordova, CA, USA or St Jude Medical, Minneapolis, MN, USA) subsequently in vessels with intermediate stenosis between 30 and 90% ( 14 , 16 , 26 ). Maximum hyperemia was induced by intravenous administration of adenosine triphosphate (140–180 μg/kg/min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This urges us to determine the quality of EAT rather than the solely thickness or volume of EAT. Recently, Yu Du and his colleagues have shown that lesion-speci c EAT volume index, but not density, seems positively and independently associated with myocardial ischemia [43]. In some way, quanti cation of epicardial fat using 3D cine Dixon MRI may play a pivotal role in determining the quality of EAT [44].…”
Section: Discussionmentioning
confidence: 99%